Reviewer Acknowledgements: Education, Equity and Evidence in Global Health - GHMJ (Global Health Management Journal), Volume 8, Number 3, 2025 - GHMJ (Global Health Management Journal) (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
The Editorial Board would like to express its sincere gratitude to the reviewers who contributed their time, insight, and scholarly judgment to the issue of the Global Health Management Journal (Vol. 8, No. 3, 2025). This issue begins by placing education at the center of global health responsibility. The opening editorial reminds us that preparing young people to engage with health challenges is not simply an academic goal, but a humanitarian one; rooted in equity, empathy, and long-term impact (Macnab, 2025). From this foundation, the perspectives section broadens the conversation and draws attention to the human and structural dimensions of health. Friendship and peer support highlight how care often emerges from relationships (Gasa et al., 2025). The discussions on children’s mental health in post-war settings (Dossen, 2025) and the future of peer review we believe will invite readers to reconsider how systems can better serve those they are meant to protect (Mosa et al., 2025). A review article in this issue challenges readers to think beyond borders when considering responsibility and harm; shaping by unequal power and policy decisions, by framing environmental exposure as an issue of justice rather than geography (Shin & Jung, 2025). The research articles then bring these broader concerns into specific contexts, offering evidence from clinical practice, educational institutions, and communities. Studies on student well-being (Yeyentimalla, 2025), faith-based pharmaceutical services (Latifah et al., 2025), tuberculosis treatment and resistance (Dewi et al., 2025 ; Santoso et al., 2025), experimental approaches to cholesterol management (Putra et al., 2025), and public understanding of vector control technologies (Herawati et al., 2025) collectively show how health outcomes are shaped by knowledge, belief, access, and trust. Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/GHMJ.08.03 Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A External Reviewers Dr. Linda Welmintje Fanggidae, ST., MT (Universitas Nusa Cendana, Indonesia) Dr. Henie Kurniawati, S.Psi., M.A., Psikolog (UIN Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia) Dr. Indriyati Hadi Sulistyaningrum, M.Sc. (Universitas Islam Sultan Agung, Indonesia) Dr. apt. Seftika Sari, S.Farm, MPH. (STIFAR Riau, Indonesia) Putu Erma Pradnyani, S.KM., M.Kes. (Universitas Pembangunan Nasional Veteran, Indonesia) Supim Wongtongtair, Ph.D. (Srinakharinwirot University, Thailand) Pharm. Tobilola O. Akingbade (North Carolina Central University, United States) dr. Mitra Handini, M.Biomed. (Universitas Tanjungpura, Indonesia) Sung-Eun Kim, Ph.D. (Oncobix.Co., Ltd., South Korea) Dr. Kahsay Hailu Negash (Adal Medical University, Somaliland) Olabode Ekerin, MD. (University of Nebraska-Lincoln, United States) Eligible reviewers will be considered for future roles on our Editorial Board, and receive Exclusive Publishing Opportunity and the chance to publish Guest Editorial Papers at no cost. Simply register on our website and select the